Directive Speech Act in Cruella 2021 Movie - Firzadika Syaufa Yardha; Ambalegin Ambalegin (LPPM Universitas Bumigora Mataram, 2022)
This research aimed at finding out the different types of directive speech act in Cruella 2021 movie. In this research, the researchers applied Searle’s theory of speech act. The researchers used qualitative method to analyze directive speech act in this research. The directive speech act is the subject of this investigation. Cruella 2021 movie is the focus of this investigation. This research contained utterances from the movie's conversation dialogue. A distinct sort of directive speech act could be found in each statement from the movie. In collecting the data, this research used non-participatory observation method. The categorization method was used to analyze the data for this research. In the analysis, the researchers found the types of directive speech act. This research had 15 data from types of directive speech act which was separated into command (3 data), request (3 data), permission (3 data), prohibition (3 data), and question (3 data). The researchers also explained the purpose of the different types of directive speech act in each utterance.